Optimización del ancho del cordón de soldadura en acero A36 en el proceso de soldadura FCAW, usando metodología Taguchi - Zavaleta Yacila, Alvaro Michel (2013)
The purpose of this investigation was to determine the optimal levels of welding current, arc voltage and welding speed simultaneously maximize the width of the weld bead and the S / N (Signal to Noise) ratio in A36 steel in the process FCAW. Design parameters of the Taguchi methodology where L9 orthogonal array selected by a total of 9 experimental runs were used. Using the S / R ratios proposed by Taguchi, it was found that 300 A current variable welding and 1000 mm / min for the welding speed is a combination which maximizes the width of the weld bead